Role of Perceived Competence and Task Interest in Learning From Negative Feedback - Shin, Dajung Daine; Kim, Sung-il; Lee, Myung-Jin; Jiang, Yi; Bong, Mimi (Frontiers in Psychology, 2022)
We used functional magnetic resonance imaging to examine the interactive effects of perceived competence and task interest on the cognitive and affective responses to negative feedback. Twenty-four undergraduates performed both interesting and uninteresting tasks and received failure feedback. The participants’ perceived competence in the task was manipulated between subjects prior to scanning with bogus feedback. The results showed that negative feedback processing was contingent upon both perceived competence and task interest. The most adaptive coping mechanism, indicated by activation in the cognitive control network and attenuation in the negative affect region, was identified for the high-competence, high-interest combination. When either competence or interest was low, signals in the cognitive control network were weaker. The most detrimental activation patterns were observed for the combination of low-competence and high-interest. Our results reveal the combination of task and learner characteristics that best harnesses the potential benefits of negative feedback and illustrate the neuroscientific mechanisms underlying this observation.